FOSTERING POSITIVE EDUCATION PRACTICES WITHIN THE FRAMEWORK OF WORK INTEGRATED LEARNING IN INDONESIAN POLYTECHNIC - Uray Endang Kusumajaya; andini linarsih; Nurul Fadillah (Universitas Tanjungpura, 2022)
The paper intends to seek the windows of opportunity fostering positive education in Indonesian Polytechnic through students' Work Integrated Learning (WIL). The approach adopts positive education that sees character traits as malleable skills that can develop with effective teaching and practices. Students' work placement in a real-world setting encourages them to apply theoretical and practical learning and, at the same time, provide them the opportunity to learn and practice life skills. Two types of data were collected for this study: a survey and interviews. Five students were interviewed on an occasion in which they were probed on how do they responded towards the aspect of WIL in the survey of student's engagement. The thirty-three items of Resilience Scale for Adults [1] results indicate that participants relatively scored high on five factors measurements on the RSA scale. It indicated that they seem to be easily more adaptable and more resilient. Whilst, the interviews confirm that student engagements in their respective field works strengthens the need for resilience and character strengths for work-related knowledge and skills.